5 Developing a specialist teaching curriculum to equip students for working in a tertiary level children's hospital. (22nd November 2019) - George, Isabella De; Tonkin, Tabitha; Hudson, Natalie; Porter, Lauren; Gowers, Nicola
Abstract : Rationale: Within specialist tertiary children's hospitals, student nurses are likely to encounter complex health conditions and specialities. Therefore, providing extracurricular teaching was developed to equip student nurses with the relevant knowledge of the patient groups they are caring for whilst on their placement. Due to the change in the NMC standards, workshops were developed as a safe environment for students to practice and learn skills needed for their proficiencies. Description: The undergraduate nursing team cover 36 wards pan trust providing support and education to student nurses whilst in trust. Whilst teaching on fundamental care and common conditions was already being provided, it was recognised that student nurses were not receiving teaching around the complex health conditions they were caring for. As a result of this, the teaching curriculum was adapted to incorporate this. This was done by combining theory and practical sessions into one session. Student numbers were also limited to 10 students a workshop, to ensure that they received more individualised and appropriate teaching. Results: We used an online survey tool to evaluate the feedback for the developed teaching curriculum. On analysis of 100 results, 95% of the students found the sessions 'extremely useful'. Students enjoyed how interactive teaching sessions were and found that by incorporating practical skills, this created a safe space for them to learn in. They also found that the teaching was beneficial alongside placement due to the relevance in practice. Students commented on the small size of the groups, highlighting the benefit of reducing group sizes. Discussion: It's evident from the feedback that developing the teaching curriculum to incorporate complex health conditions has been very useful in student education. Particularly within tertiary children's hospitals where students are likely to encounter complex health conditions and students therefore need more specialist knowledge to provide expert patient care.